2017
DOI: 10.1124/mol.117.109900
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Oleanane-Type Triterpene Hedragonic Acid as a Novel Farnesoid X Receptor Ligand with Liver Protective Effects and Anti-inflammatory Activity

Abstract: Farnesoid X receptor (FXR) and G-protein-coupled bile acid receptor 1 (GPBAR1) are two important bile acid (BA) receptors. As non-BAs drug template for GPBAR1, none of the natural oleanane-type triterpenes have been reported as FXR ligands, despite FXR and GPBAR1 having similar binding pockets for BAs. Here, we report the natural triterpene hedragonic acid that has been isolated from the stem and root of Thunb. (COT) as an effective agonist for FXR. Both biochemical amplified luminescent proximity homogeneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Although the benefits of targeting the TGR5 receptor help maintain bile acid homeostasis, TGR5 activation is also associated with risks of histopathological changes, tumorigenesis, pruritus and others . Unlike bile acids, OA is a TGR5 agonist, but not (or a weak) FXR agonist . Intradermal injection of bile acids or TGR5 agonist OA stimulated analgesia and scratching behaviour, which was attenuated in Tgr5‐KO mice but exacerbated in Tgr5‐Tg mice …”
Section: Mechanisms For Paradoxical Hepatoprotective and Hepatotoxic mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the benefits of targeting the TGR5 receptor help maintain bile acid homeostasis, TGR5 activation is also associated with risks of histopathological changes, tumorigenesis, pruritus and others . Unlike bile acids, OA is a TGR5 agonist, but not (or a weak) FXR agonist . Intradermal injection of bile acids or TGR5 agonist OA stimulated analgesia and scratching behaviour, which was attenuated in Tgr5‐KO mice but exacerbated in Tgr5‐Tg mice …”
Section: Mechanisms For Paradoxical Hepatoprotective and Hepatotoxic mentioning
confidence: 99%
“…[83][84][85] Unlike bile acids, OA is a TGR5 agonist, but not (or a weak) FXR agonist. 17,59,86 Intradermal injection of bile acids or TGR5 agonist OA stimulated analgesia and scratching behaviour, which was attenuated in Tgr5-KO mice but exacerbated in Tgr5-Tg mice. 87,88 TGR5 activation by OA induced the expression of IL-1β and TNFα in the murine macrophage cell line RAW264.7 or in murine Kupffer cells.…”
Section: Tgr5 Activation In Oa Hepatoprotection and Hepatotoxicitymentioning
confidence: 99%
“…Oleanolic acid also exhibits antitumor effects in various cancers, including leukemia (3), pancreatic cancer (4), gallbladder cancer (5), melanoma (6), breast cancer (7), liver cancer (8), lung cancer (9), and osteosarcoma (10), by inducing apoptosis and cellcycle arrest or through the radiosensitizing effect of radiotherapy. Some potential targets for oleanolic acid have been reported in cancer and other diseases, such as aldo-keto reductase family member 1B10 (AKR1B10), CD81, G-protein coupled bile acid receptor 1, 11b-hydroxysteroid dehydrogenase type 1, protein tyrosine phosphatase 1B, and cell division cycle 25 phosphatase (11)(12)(13)(14)(15)(16). AKR1B10 was suggested as a therapeutic target in colon cancer.…”
Section: Introductionmentioning
confidence: 99%
“…C. orbiculatus has been traditionally prescribed as a herbal remedy for bacterial infection, insecticidal, and rheumatoid arthritis [3,4]. Previous pharmacological studies has shown that these extracts containing diverse phytochemical components such as sesquiterpenoids, diterpenoids, tri-terpenoids, alkaloids, flavonoids, and phenolic compounds [5][6][7][8][9][10] exhibit various biological activity such as antitumor [11][12][13][14], antioxidant [9], antinociceptive [15], antiatherosclerosis [16], neuroprotective [17], and anti-inflammatory [18] effects. Although a variety of biological activities of C. orbiculatus extracts reported in the literatures, whether any phytochemical component contributes to their biological mechanisms other than celastrol, which is the main triterpenoid compound of C. orbiculatus [19,20], has been discussed limitedly so far.…”
Section: Introductionmentioning
confidence: 99%